2014
DOI: 10.1148/rg.345130131
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted Imaging of Gynecologic Tumors: Diagnostic Pearls and Potential Pitfalls

Abstract: Conventional magnetic resonance (MR) imaging has an established role in gynecologic imaging. However, increasing clinical demand for improved lesion characterization and disease mapping to optimize patient management has resulted in the incorporation of newer sequences, such as diffusion-weighted (DW) imaging, into routine protocols for pelvic MR imaging. DW imaging provides functional information about the microenvironment of water in tissues, hence augmenting the morphologic information derived from conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 66 publications
4
50
0
1
Order By: Relevance
“…However, recent studies suggest that MRI through diffusion and post-contrastographic sequences, represent emerging valuable technique for the differential diagnosis between degenerate leiomyoma and sarcomas [21,22,[25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies suggest that MRI through diffusion and post-contrastographic sequences, represent emerging valuable technique for the differential diagnosis between degenerate leiomyoma and sarcomas [21,22,[25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion Weighted Imaging (DWI) in recent studies has shown promising results in the differential diagnosis between benign and malignant gynecological tumours [22][23][24][25][26] . Nevertheless, using DWI in the diagnosis of uterine sarcomas is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted magnetic resonance imaging (DW-MRI) shows higher sensitivity for small lesions, but the specificity may be limited by diffusion restriction [31]. Also, 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/CT imaging is used to evaluate peritoneal metastasis in advanced ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, there are very few studies from India using DWI and ADC as a biomarker in tumors of the brain and cervical cancer. [27][28][29][30][31] With this view in mind, we wanted to test the utility of a simple, functional study parameter which can be easily done along with conventional MRI at a larger scale at the national level to predict progression of disease in glial tumors post treatment. With a view to refine assessment of tumor status during follow-up after radiotherapy and surgery of glial tumors, we studied the role of ADC for predicting tumor response in patients.…”
Section: Introductionmentioning
confidence: 99%